2000
DOI: 10.1359/jbmr.2000.15.4.763
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Skeletal Kinetics Between Vertebral and Humeral Bone Measured by 18F-Fluoride Positron Emission Tomography in Postmenopausal Women

Abstract: We have sought to investigate regional differences in skeletal kinetics between lumbar vertebrae and the humerus of postmenopausal women with 18 F-fluoride positron emission tomography (PET). Twenty-six women, mean age 62 years, had dynamic PET scans of the lumbar spine and lower humerus after the injection of 180 MBq 18 F-fluoride ion. Plasma arterial input functions (IFs) were calculated from a mean IF measured arterially from 10 women and scaled according to late individual venous activity. Vertebral and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…In this study, we found that the mean SUVmax in the lumbar spine was 2.5 times greater than that in the humeral shaft in postmenopausal women. These results were similar to previous reports using compartmental analysis [e.g., fluoride clearance to bone mineral (Ki), and blood flow and the unidirectional extraction fraction of fluoride (K1)] and Cook et al have reported that Ki and K1 were significantly greater at the lumbar spine compared with the humeral shaft [12,31]. Ki was a function of both K1, which reflects bone blood flow, and the fraction of the tracer that undergoes specific binding to the bone mineral.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that the mean SUVmax in the lumbar spine was 2.5 times greater than that in the humeral shaft in postmenopausal women. These results were similar to previous reports using compartmental analysis [e.g., fluoride clearance to bone mineral (Ki), and blood flow and the unidirectional extraction fraction of fluoride (K1)] and Cook et al have reported that Ki and K1 were significantly greater at the lumbar spine compared with the humeral shaft [12,31]. Ki was a function of both K1, which reflects bone blood flow, and the fraction of the tracer that undergoes specific binding to the bone mineral.…”
Section: Discussionsupporting
confidence: 92%
“…2a) and at the right humeral midshaft as an area representing a predominantly cortical-rich bone site in the coronal plane (Fig. 2b) [12][13][14]. All studies were evaluated semiquantitatively using the maximum standardized uptake value (SUVmax).…”
Section: Discussionmentioning
confidence: 99%
“…Zooming in further, in 18 F-Fluoride PET scanning it is believed that PET intensity reflects the activities of osteoblasts and osteoclasts, and at least in animal experiments, microdamage can be detected (147). Regional bone perfusion and turnover studies with bone turnover markers as a reference have been performed comparing different skeletal sites in treatment-naïve and patients with osteoporosis on treatment with various antiosteoporotic agents (148)(149)(150)(151)(152)(153)(154). The long term precision reflected by the coefficients of variation (12.2-26.6%) and intraclass correlation (0.44-0.85) for 18 F-Fluoride PET parameters has been reported to be equivalent to that observed for biochemical bone turnover markers (155).…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…18 Ffluoride PET has been used to investigate regional bone metabolism in patients with metabolic bone disease (23,24,28,31,33) and to evaluate therapies for these diseases (30,33). In addition, important differences in remodeling activity between cortical and trabecula-rich sites can be investigated (26). 18 F-fluoride PET may also have an important role in the investigation of neovascularization after allogenic bone grafting, periprosthetic bone formation after joint replacement (35)(36)(37), and fracture healing (38).…”
Section: See Page 1808mentioning
confidence: 99%